Pengaruh pemberian klorofilin berbagai dosis terhadap indeks fagositosis makrofag dan kadar nitric oxide mencit BALB/c yang diinfeksi dengan Salmonella typhimurium - Arum, Puspito; Suromo, Lisyani B; Puruhita, Niken (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Immune responses to eliminate Salmonella infection are by activating macrophage and by producing NO. Chlorophyllin is a chlorophyll derivate that has immunomodulator properties. Objective: The aim of this study was to prove effect of chlorophyllin in macrophage phagocytosis index and NO level. Methods: A post test only controlled group design was conducted in 5 groups Balb/c mice (negative control, positive control, dosage 100 µg/200 g BW, dosage 200 µg/200 g BW and dosage 380 µg/200 g BW). Macrophage phagocytosis index was measured by counting cells that phagocyte latexs particles. NO level was measured by Griess method. Macrophage phagocytosis index difference was analyzed by one way anova and NO level deference was analyzed by Kruskall-Wallis test (α 0,05).Results: Means of macrophage phagocytosis index were 0,7(±0,80), 1,8(±0,80), 2(±0,22), 2,5(±0,43) and 3,2(±0,68) respectively in negative control, positive control, chlorophyllin dosage 100 µg/g BW/day, 200 µg/g BW/day and 380 µg/g BW/day. There was a significant difference of macrophage phagocytosis index between group (p 0,000). Mean of NO level were 0,4 µM(±0,10), 0,6 µM(±0,60), 0,8 µM(±0,64), 0,6 µM(±0,67) and 0,4 µM(±0,26) respectively in negative control, positive control, chlorophyllin dosage 100 µg/g BW/day, 200 µg/g BW/day and 380 µg/g BW/day. There was no difference of NO level between group (p 0,813).Conclusion: There was a significant difference of macrophage phagocytosis index between chlorophyllin administered group and control. The higher chlorophyllin dosage, the higher macrophage phagocytosis index. Therewas no difference of NO level between chlorophyllin administered group and control.